Minimal residual disease guided radical chemoradiotherapy combined with immunotherapy after neoadjuvant immunochemotherapy followed by adjuvant immunotherapy for esophageal squamous cell cancer (ECMRD-001): a study protocol for a prospective cohort study - Wang, Hesong; Zhang, Xueyuan; Zhao, Xiaohan; Song, Chunyang; Deng, Wenzhao; Shen, Wenbin (Frontiers in Immunology, 2024)
Introduction For locally advanced, inoperable esophageal cancer, concurrent chemoradiotherapy (CCRT) becomes the norm. Combining immunotherapy with radiotherapy has been shown to improve efficacy. Circulating tumor DNA (ctDNA) is a strong predictor of effectiveness and tumor recurrence and is indicative of minimal residual disease (MRD). Patients with inoperable stage II-III esophageal squamous cell carcinoma (ESCC) are enrolled in the ECMRD-001 trial to evaluate changes in MRD status before and after CCRT combined with immunotherapy and adjuvant immunotherapy following neoadjuvant immunochemotherapy. Methods and analysis The ECMRD-001 trial is a prospective cohort study. Eligible patients will receive radical concurrent chemoradiotherapy combined with immunotherapy after neoadjuvant immunochemotherapy, followed by adjuvant immunotherapy for at least one year. Follow-up will be up to three years. MRD-related blood and tissue samples and T-cell immunohistobank related blood and tissue samples collected before, during and after treatment and follow-up will be grouped into sample collection time points. The relationship between MRD status at different time points and treatment efficacy is the primary outcome. Correlation between MRD status and immune microenvironment, radiotherapy dose, and tumor recurrence are the secondary outcomes. Examination of ctDNA mutations is the exploratory outcome. Discussion ctDNA-based MRD may be a potential predictive marker for the efficacy and tumor recurrence of inoperable ESCC patients. Elevated ctDNA-MRD may predict tumor recurrence earlier than imaging. ctDNA-based MRD analysis and ctDNA-based MRD guided diagnosis and treatment should be implemented into clinical practice to improve efficacy and reduce tumor recurrence of inoperable stage II-III ESCC. Trial registration The ECMRD-001 study has been registered at ClinicalTrials.gov as NCT05952661 (July 19, 2023), https://classic.clinicaltrials.gov/ct2/show/NCT05952661.